New Aderidae (Coleoptera: Tenebrionoidea) from Baltic and Bitterfeld amber - Alekseev, Vitalii I.; Grzymala, Traci L. (Zootaxa, 2015)
Nine extinct species and one genus of aderid beetles (Coleoptera: Tenebrionoidea: Aderidae) are described from Baltic and Bitterfeld amber from Germany, Russia (Kaliningrad), Poland, and Denmark. These new species include: Escalerosia igori sp. nov., Picemelinus irinae sp. nov., Vanonus ulmerigicus sp. nov., Vanonus aestiorum sp. nov., Cnopus kraxtepellenensis sp. nov., and four species from the extinct genus Palaeocnopus gen. nov.: P. densipunctatus sp. nov., P. saeticornis sp. nov., P. glabricornis sp. nov., and P. mara sp. nov. A key to the species of Palaeocnopus in amber is provided. The newly described taxa of these ant-like leaf beetles are photographed, illustrated, and compared with extinct and related extant representatives of the genera.